Di Antara Tekanan, Rasa Aman dan Keheningan: Fenomenologi dan Politik Afek Orang Muda Queer dalam Bekerja di Indonesia - Yulida Pangastuti (Jurnal Studi Pemuda, 2025)
This article analyses how young queer people in Indonesia navigate a world of work governed by heteronormative, religious and moral norms. Drawing on developments in Queer analysis within the tradition of Critical Youth Studies, this research relies on Mary Anna Robertson's thinking to understand the transition of queer youth as a non-linear, fragile process of becoming, shaped by institutional relations, rather than as a linear progression towards professional stability. Conceptually, this analysis also draws on Sara Ahmed's concept of orientation, Eve Sedgwick's theory of the closet, and Judith Butler's notion of performativity. These three concepts help to reveal how work transitions are experienced as processes of negotiating the direction of life, visibility, and bodily presence in everyday work. Affective orientation shapes choices of safe spaces and relationships, closet practices enable strategic management of knowledge about oneself, while professional performativity normalises the body while opening up limited spaces for resistance. Based on semi-structured interviews with seven young queer professionals in various sectors, this study shows that work compatibility is constructed as a temporary affective-moral achievement. Professionalism is thus understood as the result of ongoing queer negotiations so that the body can be present, work, and be recognised without fully submitting to normative order.